Effect of Varying Packet Interval Time on Multihop Routing Protocol in Wireless Sensor Network - Sharma, Namita; Kakkar, Parveen (Discoveries in Agriculture and Food Sciences, 2015)
The distinguishing characteristics of sensor networks are that they are basically infrastructure less, self configured wireless networks used to monitor environmental conditions such as temperature, sounds etc. which and communicate with each other using radio signals. The sensor nodes contain non chargeable batteries and they in several rounds of data transmission they soon get drained out of energy. Depending upon the given conditions, the sensor nodes in the random network may be hundreds or thousands in number .Each individual node has its own sensing and computing devices along with the radio transceivers and power components. In this paper, effect of changing the packet interval time on the energy consumption, throughput of the proposed multihop routing protocol is analyzed. It is a substantial fact that change in the packet interval time when the packets are to be transmitted to further levels of hierarchy has a relation with the latency and load balancing of the network. The simulation results show that with the variation of the packet interval time , the throughput attains a peak value at a certain point , then decreases alternately whereas the energy consumed by the protocol remains constant for a particular time interval but the value increases as the packet transmission time interval increases.